Thermophysical properties for the published article "Experiments and modelling on ASDEX Upgrade and WEST in support of tool development for tokamak reactor armour melting assessments" - Tolias, Panagiotis; Ratynskaia, Svetlana; Paschalidis, Konstantinos (Royal Institute of Technology, 2022)
In order to model the macroscopic metallic melt motion realized in the poor-versus-efficient thermionic emitter leading edge exposures in the ASDEX-Upgrade outer divertor [1], the material library of the MEMENTO melt dynamics code, that previously only concerned tungsten [2] and beryllium [3], had to be extended to iridium and niobium.

Reliable experimental data have been analyzed for the latent heats, specific isobaric heat capacity, electrical resistivity, thermal conductivity, mass density, vapor pressure, work function, total hemispherical emissivity and absolute thermoelectric power from the room temperature up to the normal boiling point of iridium and niobium as well as for the surface tension and the dynamic viscosity across the liquid state. Analytical expressions are recommended for the temperature dependence of these thermophysical properties, which involve high temperature extrapolations given the absence of extended liquid iridium and liquid niobium measurements. The analytical expressions, the details of their construction and the main references are included in the accompanying pdf.

[1] S. Ratynskaia, K. Paschalidis, P. Tolias, K. Krieger, Y. Corre, M. Balden, M. Faitsch, A. Grosjean, Q. Tichit, R.A. Pitts, the ASDEX-Upgrade team, the WEST team and the Eurofusion MST1 team, "Experiments and modelling on ASDEX Upgrade and WEST in support of tool development for tokamak reactor armour melting assessments", Nucl. Mater. Energy 33 (2022) 101303.
[2] P. Tolias, "Analytical expressions for thermophysical properties of solid and liquid tungsten relevant for fusion applications", Nucl. Mater. Energy 13 (2017) 42.
[3] P. Tolias, "Analytical expressions for thermophysical properties of solid and liquid beryllium relevant for fusion applications", Nucl. Mater. Energy 31 (2022) 101195.

SR, PT acknowledge the financial support of the Swedish Research Council under Grant No 2021-05649. The work has also been performed within the framework of the EUROfusion Consortium, funded by the European Union via the Euratom Research and Training Programme (Grant Agreement No 101052200 - EUROfusion). Views and opinions expressed are however those of the authors only and do not necessarily reflect those of the European Union or European Commission. Neither the European Union nor the European Commission can be held responsible for them.
Keywords: thermophysical properties, niobium, iridium, thermionic emission, melt motion, tokamak; Physical Sciences; Fysik